Nursing cooperation in left ventricular assist device implantation for a patient with ventricular aneurysm and thrombus after percutaneous coronary intervention (PCI术后合并室壁瘤和血栓的左心衰竭患者行左心室辅助装置植入的护理配合) - FU Chaojuan (付朝娟); XIA Yesong (夏叶松); ZOU Xiufang (邹秀芳) (中西医结合护理)
This paper summarized the nursing cooperation in left ventricular assist device (LVAD)implantation for a patient with ventricular aneurysm and thrombus after percutaneous coronary intervention (PCI), including the case analysis and evaluation before surgery, choice of surgical method and perioperative nursing cooperation. The foundation of a successful surgery consists of precise perioperative nursing and concise surgical coordination. The practice of nursing cooperation in left ventricular assist device implantation is help to improve the comprehensive skills of specialist nurse in cardiac surgery. (总结1例经皮冠状动脉介入(PCI)术后合并室壁瘤及血栓的左心衰竭患者行左心室辅助装置(LVAD)植入的手术配合及护理经验, 包括术前病例分析和评估、手术方式的选择、术中配合等。完善周密的围术期护理和简洁精准的手术配合是手术成功的基础, 同时该手术的护理配合也完善了手术室心外科专科护士的综合能力的培养。)